2019
DOI: 10.1016/j.arabjc.2015.07.014
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of polyphenol composition, antioxidant and antimicrobial properties of various extracts of Date Palm Pollen (DPP) from two Tunisian cultivars

Abstract: This study aimed to investigate and compare the total phenolic (TPC) and flavonoid (TFC) contents and antioxidant and antibacterial activities of different extracts recovered from Date Palm Pollen collected from Tunisian cultivars of Kerkennah (DPP-K) and Tozeur (DPP-T) using various solvents, including hexane, chloroform, ethyl acetate, acetone, ethanol and water. The results revealed that DPP-T had higher TPC than DPP-K for all solvent extracts, except for hexane, with a value of 237.74 ± 9.58 mg GAE/g fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
87
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 149 publications
(126 citation statements)
references
References 44 publications
4
87
0
2
Order By: Relevance
“…On the other hand, α-tocopherol, one of the major sperm antioxidants, was established to be abundant in spermatozoa membrane (Suleiman et al, 1996;Surai et al, 2000) and protect sperm motility from oxidative harm (Brzezińska-Ślebodzińska et al, 1995). Besides, date palm pollen suspension was reported to have potent antimicrobial, antifungal and anti-toxicant activities (Aba Al-Khail et al, 2003;Shakibaa et al, 2011;Daoud et al, 2015) and these effects could improve postthawing semen quality through reduction of bacterial growth in the semen extender.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, α-tocopherol, one of the major sperm antioxidants, was established to be abundant in spermatozoa membrane (Suleiman et al, 1996;Surai et al, 2000) and protect sperm motility from oxidative harm (Brzezińska-Ślebodzińska et al, 1995). Besides, date palm pollen suspension was reported to have potent antimicrobial, antifungal and anti-toxicant activities (Aba Al-Khail et al, 2003;Shakibaa et al, 2011;Daoud et al, 2015) and these effects could improve postthawing semen quality through reduction of bacterial growth in the semen extender.…”
Section: Discussionmentioning
confidence: 99%
“…AlFarasi et al (2005) and Mansouri et al (2005) reported the potent antioxidant activity of the aqueous extract of dates which was attributed its inclusion to the wide range of phenolic compounds including p-coumaric, ferulic and sinapic acids, flavonoids and procyanidins. Palm pollen has also been recognised as a rich source of phytochemicals and nutrients mainly carotenoids and flavonoids (Daoud et al, 2015). Fresh pollen has a highly nutritive value as it is rich in mineral, multi-vitamins, sugars, lipids, growth factors and more than 100 enzymes and cofactors (Hassan, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…In this part, we used the same protocol as ascribed by Daoud et al (2015). Bacterial and fungal strains showing sensitivity to tested extracts are therefore selected to determine the minimum inhibitory and bactericidal/ fungicidal concentrations.…”
Section: Antimicrobial Activity By Agar Diffusion Method Determinatimentioning
confidence: 99%
“…The kill-time analysis is often applied, by following the decrease of the bacterial cells growth, over time, due to the effect of a definite extract concentration as reported by our laboratory (Daoud et al, 2015). Each test was performed twice.…”
Section: Kill-time Analysismentioning
confidence: 99%
See 1 more Smart Citation